Literacy Screening Among Latino/a and Dual Language Learner Kindergarteners: Predicting First Grade Reading Achievement. Issue 3 (3rd July 2017) - Edyburn, Kelly L.; Quirk, Matthew; Felix, Erika; Swami, Sruthi; Goldstein, Ariel; Terzieva, Antoniya; Scheller, Jennifer
ABSTRACT: This study examined the relative contributions of Latino/a children's ( N = 102) school readiness and early literacy skills during kindergarten in predicting first grade reading achievement. By using discriminant function analyses, the current study identified a set of areas to assess that could be used to effectively screen children during kindergarten to distinguish those that might benefit most from early and targeted literacy supports. Results suggest that receptive vocabulary, phonological awareness, and word reading were the areas in kindergarten that provided strong predictive power for understanding children's end of first grade reading achievement. These results provide important insights into an efficient assessment framework literacy educators can utilize to effectively monitor and support the early literacy development of Latino/a students.